Contextual Concrete Media for Improving Subtraction Skills in Elementary Students: Media Konkret Kontekstual untuk Pemahaman Operasi Pengurangan Siswa Sekolah Dasar - Kusumawati, Anggriani; Ishartiwi; Handoyo, Rendy Roos (Indonesian Journal of Innovation Studies, 2025)
Background: Mathematics learning in early elementary grades often faces challenges, particularly in teaching abstract concepts like subtraction to students with learning difficulties. Specific background: Many students experience low understanding and motivation, leading to poor learning outcomes that fall below the minimum mastery criteria. Knowledge gap: Few studies focus specifically on the use of contextual, hands-on media for subtraction skills in second-grade students with learning difficulties. Aim: This study investigates the use of a contextual concrete media, the Counting Box, to strengthen conceptual understanding of subtraction. Results: A quasi-experimental one-group pretest-posttest design was used with five students. Results revealed a significant improvement in posttest scores, with an average N-Gain score of 0.82 (82%), categorized as high. Students demonstrated greater focus, engagement, and success in solving subtraction problems within the 1–20 range. Novelty: The study presents a practical, engaging 3D learning tool designed specifically for students with learning difficulties. Implications: Findings suggest that teachers can adopt Counting Box as a classroom strategy to support inclusive education, improve conceptual understanding, and foster active participation in mathematics learning. Highlights: Students showed a 36% average score improvement after using Counting Box. The contextual design helped make subtraction concepts more concrete and engaging. Teachers reported high classroom engagement and improved focus among students. Keywords: Contextual Learning, Concrete Media, Counting Box, Subtraction Skills, Learning Difficulties